2011
DOI: 10.1053/j.ajkd.2010.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Donor Exchange Programs in Kidney Transplantation: Rationale and Operational Details From the North Central Donor Exchange Cooperative

Abstract: The increasing need for kidney transplants has led to innovations such as donor exchange programs. These programs offer transplant recipients with incompatible donors an opportunity to receive a compatible kidney. They also provide an alternative to costly desensitization protocols that have unproven long-term outcomes. Donor exchange programs have multiple options including simple two-pair exchanges, more complicated domino exchanges, or chain donations. The United States is currently limited by regional prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…Presently, there are multiple exchange programs, some of which are based on geography. There are different models for producing a match, which for example include PRA, blood type, and unacceptable antigens . However, here we have identified a larger number of potentially important variables which may be helpful to include as well.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Presently, there are multiple exchange programs, some of which are based on geography. There are different models for producing a match, which for example include PRA, blood type, and unacceptable antigens . However, here we have identified a larger number of potentially important variables which may be helpful to include as well.…”
Section: Discussionmentioning
confidence: 98%
“…Identifying modifiable pretransplantation risk factors of DGF (e.g., CIT) is important for optimization of long‐term graft outcomes. This issue is of increasing importance, as LD kidneys are now experiencing increased CIT with national exchange programs .…”
Section: Discussionmentioning
confidence: 99%
“…After a complete clinical evaluation to establish her good health, her proposal was accepted and in April 2015 the first live kidney transplant from a Samaritan donor in Italy took place. This particular type of donation gave the start to a "chain donation" kidney transplantation (Akkina et al, 2011), all donors and recipients continue to do well postoperatively, continuing follow-up. The donor did not develop a depressive disorder during the 12-month follow up period, she declared to be grateful for the opportunity to help someone.…”
Section: Samaritan Donation: a New Challenge For The Italian Transplamentioning
confidence: 99%
“…Chan et al showed that with the exception of recipients aged 18-39 years, who had the best outcomes with donors aged 18-39 years, living donors aged between 18-64 years has minimal effect on allograft survival [23]. Some programs have implemented limits such that they would not match donors to a recipient more than 20 years younger than the candidate's incompatible donor [24].…”
Section: Financial and Ethical Considerationsmentioning
confidence: 99%